Reactive oxygen species as a trigger of the infarct-limiting effects of early hypoxic preconditioning rat myocardium - A. S. Sementsov; A. V. Krylatov (Acta Biomedica Scientifica, 2016)
It is believed that reactive oxygen species (ROS) are involved in the performance of this adaptive hepatoprotective effect phenomenon. However, the role of ROS in the signaling mechanism of the early hypoxic preconditioning (early HP) and the contribution of individual types of oxygen radicals in the infarct-limiting effect of early HP remains uncertain to the end. Objective was to investigate the role of various types of reactive oxygen species in the signaling mechanism of the infarct-limiting effect of early hypoxic preconditioning. We investigated the role of reactive oxygen species in the signaling mechanism of early HP in vivo. Adaptation of animals was conducted with 6 transient hypoxia-reoxygenation sessions before prolonged ischemia (45 min) and reperfusion (120 min). Low molecular weight antioxidants were administered 15 minutes prior to the HP. We found out that pretreatment with the nonselective antioxidant indirect action of N-(2-mercaptopropionyl)-glycine and "trap" of hydroxyl radicals 1,3-dimethylthiourea completely eliminated the infarct-limiting effect of adaptation. Administration of antioxidants tempol and trolox, as well as the use of N-(2-mercaptopropionyl)-glycine after HP had no effect on the protective effect of adaptation. Consequently, reactive oxygen species, including hydroxyl radical, operate as the trigger function in the signaling mechanism of early HP.